(untitled) (JURNAL PROTEKSI KESEHATAN, 2020)
Each year more than 300,000 women die from cervical cancer more than half a million women are diagnosed. Every minute, a woman is being ionogized. Cervical cancer is one of the biggest threats to women’s health. Method; analytical survey research method with cross sectional approach. The population of this study were all women of childbearing age in the work area , totaling 117 people with a sample size of 54 respondents using proportional stratified random sampling technique. Sempel used the total population technique, namely the entire population of the chi-square statistical test. . Result; results of statistical tests, namely the Chi-square, concluded that there was a relationship between husband’s support and IVA examination at PUS (p = 0.006 <α = 0.05),. and (p = 0.624> α 0.05), which means that economic status has no influence on the effect of IVA on EFA. and (p = 0.006 <α 0.05) which means that there is an effect of maternal attitudes with IVA examinations at PUS. Conclusion; There is a relationship between partner support, economic status and maternal attitudes with IVA examination at PUS.